Visual Basic 2005 : The Complete Reference - Petrusha, Ron (New York McGraw-Hill, 2005)
Covers the core language of Visual Basic, including grammar, operators, value-types, classes, interfaces, data structures and collections, GUI components, debugging, and more. This book helps readers learn to build robust applications for Windows and the Web.
Include Index.
The Complete Reference.
Keywords: Visual Basic (Computer program language) -- BASIC (Computer program language)